1996
DOI: 10.1038/ki.1996.345
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection-enhanced chronic kidney allograft rejection is linked with intercellular adhesion molecule-1 expression

Abstract: In human kidney allografts, association of acute rejection and glomerulopathy with cytomegalovirus (CMV) infection has been demonstrated. To investigate the effect of CMV infection on the development of experimental chronic kidney allograft rejection, heterotopic kidney allografts from DA (Ag-B4, RT1a1) rat donors to WF (Ag-B2, RT1u) rat recipients were used. The animals received cyclosporine A (CsA) 5 mg/kg/day s.c. either for 1 or 12 weeks. Two groups of recipients were infected with 10(5) plaque-forming uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…Investigations examining the influence of HCMV on immunomodulating molecules on infected cells identified a marked increase in ICAM-1 cellsurface expression as well as mRNA levels in endothelial cells and fibroblasts (Grundy & Downes, 1993;Sedmak et al, 1994;Ito et al, 1995;Burns et al, 1999;Knight et al, 1999Knight et al, , 2000. The in vivo relevance of cytomegalovirus-mediated ICAM-1 induction in the development of vascular lesions is strongly supported by results obtained with the rat model, where it has been shown that prolonged expression of ICAM-1 after infection of kidney allograft recipients with rat cytomegalovirus correlated with accelerated chronic allograft nephropathy (Yilmaz et al, 1996;Kloover et al, 2000).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Investigations examining the influence of HCMV on immunomodulating molecules on infected cells identified a marked increase in ICAM-1 cellsurface expression as well as mRNA levels in endothelial cells and fibroblasts (Grundy & Downes, 1993;Sedmak et al, 1994;Ito et al, 1995;Burns et al, 1999;Knight et al, 1999Knight et al, , 2000. The in vivo relevance of cytomegalovirus-mediated ICAM-1 induction in the development of vascular lesions is strongly supported by results obtained with the rat model, where it has been shown that prolonged expression of ICAM-1 after infection of kidney allograft recipients with rat cytomegalovirus correlated with accelerated chronic allograft nephropathy (Yilmaz et al, 1996;Kloover et al, 2000).…”
Section: Discussionsupporting
confidence: 55%
“…However, the pathogenic mechanisms by which HCMV infection contributes to these processes remain to be elucidated. Several studies indicate that vascular injury could result from HCMV-triggered, immunologically mediated processes, in particular in transplant patients (Koskinen et al, 1996;Yilmaz et al, 1996;Lautenschlager et al, 1997b;Martelius et al, 1998;Waldman et al, 1998). Investigations examining the influence of HCMV on immunomodulating molecules on infected cells identified a marked increase in ICAM-1 cellsurface expression as well as mRNA levels in endothelial cells and fibroblasts (Grundy & Downes, 1993;Sedmak et al, 1994;Ito et al, 1995;Burns et al, 1999;Knight et al, 1999Knight et al, , 2000.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upregulation of adhesion molecules on infected ECs may facilitate attachment of monocytes and neutrophils via ELAM1 antigen and could contribute to graft injury (166). Similar increases in ICAM1 have been observed in vivo in CMV-infected renal allografts, in which enhanced chronic kidney allograft rejection is linked to ICAM1 (167). CMV infection of mice in vivo or ECs in vitro induces IL-6 production and activates MCP-1, further increasing inflammation.…”
Section: Cytokine Production In CMV Infectionsupporting
confidence: 54%
“…CMV infection leads to inflammatory reactions such as severe colitis, retinitis, or pneumonitis (24). In addition, strong evidence has been provided that CMV may be involved in the development of allograft glomerulopathy and chronic rejection in organ transplant recipients (25)(26)(27), although the mechanisms underlying this association remain elusive.…”
Section: Implication Of γδ T Cells In the Human Immune Response To Cymentioning
confidence: 99%